Determination of Bentonite’s Flow Limit Using Cylinder Strength Test and Suspension Settling Model - Setiadjie, Samuel Jemmy; Widjaja, Budijanto; Putra, Mayolus Musa; Anandito, Atharayhan (Himpunan Ahli Teknik Tanah Indonesia, 2025)
Cohesive soils exhibit complex behavior characterized by distinct transitional boundaries between different states. One of the boundaries is the flow limit (FL), which is the transition between the viscous liquid and suspension states. Currently, there are no specific standard tests to determine the flow limit. Most previous studies have used the undrained shear strength (cu) value to determine the FL value. This study employed two different approaches to obtain the FL value: first, using the cylinder strength test (CST), which approaches from the viscous state, and second, using the suspension settling model, which approaches from the suspension state. There are five variations of samples for each test: 100% bentonite, 90% bentonite and 10% sand, 80% bentonite and 20% sand, 70% bentonite and 30% sand, and 60% bentonite and 40% sand. The cylinder test was conducted with three different cylinder diameters: 30 mm, 40 mm, and 50 mm. For the suspension settling model, five solid concentrations were used, namely 0.5%, 0.4%, 0.3%, 0.2%, and 0.1%, for each sample. The results show that the CST for bentonite suspension gave higher results than the other; meanwhile, the suspension settling model is the most conservative. The FL value from the CST test ranges from 3.33 to 4.9 times higher than the liquid limit (LL); the suspension settling model yielded values of 1.9 to 2.6 times higher than LL. The results are higher than those in previous studies, which can be attributed to differences in apparatus capacities used to determine the cu value, variations in bentonite mineral compositions, and different estimation approaches. Although in this research the range of FL values is still vast, this study has provided insights from two different approaches. This research still has various development opportunities, such as mineralogy effect and new method development to divine the FL value.